German unification : economic issues - Lipschitz, Leslie; McDonald, Donogh (Washington, D.C. : International Monetary Fund, 1990)
The book is an IMF publication on the works of various scholars on German unification. It also examines the economic developments in the Federal Republic of Germany and that of German Democratic Republic and the economic implications of the unification of German both domestically and internationally.
"December 1990."
Includes bibliographical references.
usc 23/06/2017
Loans
Keywords: Germany (West); Germany (West); Germany (East); Germany (East); Germany